Welfare of American mink, red and Arctic foxes, raccoon dog and chinchilla kept for fur production - EFSA Panel on Animal Health and Welfare (AHAW); Søren Saxmose Nielsen; Julio Álvarez; Anette Ella Boklund; Sabine Dippel; Fernanda Dorea; Jordi Figuerola; Miguel Ángel Miranda Chueca; Virginie Michel; Eleonora Nannoni; Romolo Nonno; Anja B. Riber; et al. (EFSA Journal, 2025)
Abstract This Scientific Opinion (SO) addresses a mandate from the EC regarding welfare of the following animals when farmed for their fur: (i) American mink (Neogale vison or Neovison vison), (ii) Red fox (Vulpes vulpes, also known as ‘silver fox’), (iii) Arctic fox (Vulpes lagopus, also known as ‘blue fox’), (iv) Raccoon dog (Nyctereutes procyonoides, also known as ‘Finnraccoon’) and (v) Chinchilla (Chinchilla lanigera). The request was to identify the most relevant welfare consequences (WCs) for each species and to determine whether these could be prevented or substantially mitigated in the current husbandry systems. ‘Current system’ refers strictly to the cage systems and cage dimensions as described in the EFSA Technical report produced under this mandate, as there was no or very limited information available on animals kept in alternative farming systems. Using information obtained from a review of literature, consultations with stakeholders and consideration by EFSA experts, the SO addresses for each species these WCs along with their underlying hazards and potential preventive or mitigating measures. In all species, Restriction of movement, Inability to perform exploratory or foraging behaviour, and Sensorial under‐ and overstimulation were selected as the most relevant WCs, sharing common hazards linked to current cage size and barrenness. Species‐specific WCs include: soft tissue lesions and integument damage (mink), and handling stress (mink and foxes); locomotory disorders (Arctic fox); group stress (red fox), locomotory disorders and isolation stress (raccoon dog); and inability to perform comfort behaviour, resting problems and predation stress (chinchilla). In the majority of cases, it is concluded that neither prevention nor substantial mitigation of the identified WCs is possible in the current system. The SO also includes conclusions on limited or substantial mitigation measures in the current system and, when not possible, on substantial mitigating measures which would require a change to a different system.